2008
DOI: 10.2109/jcersj2.116.1079
|View full text |Cite
|
Sign up to set email alerts
|

Controlled crystallization in Ge-(Sb/Ga)-(S/Se)-MX glasses for infrared applications

Abstract: In this paper, the last glass-ceramics recently made from chalco-halide glasses is presented. Various glass-ceramics were obtained from compositions belonging to different systems such as Ge-(Sb/Ga)-(S/Se)-MX (MX: alkali halide). XRD experiments and SEM observations were performed to determine the crystallization mechanism in these chalcogenide glasses. While alkali halide such as CsCl is rejected from the glassy network in antimony based glasses leading to its crystallization, some gallium based glasses prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Observations of the samples by SEM show that particles start to crystallize when the glass is shaped at 435°C. Then, these particles gathered under aggregates of a hundred nanometers constituted of smaller particles, as demonstrated in previous works 23 . Pictures of the molding experiments at 480°C show a highly crystallized glass, which corresponds to the crystallization of second phase observed by DSC measurements, which is obviously GeSe 2 according to the diffraction pattern of GC 3 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Observations of the samples by SEM show that particles start to crystallize when the glass is shaped at 435°C. Then, these particles gathered under aggregates of a hundred nanometers constituted of smaller particles, as demonstrated in previous works 23 . Pictures of the molding experiments at 480°C show a highly crystallized glass, which corresponds to the crystallization of second phase observed by DSC measurements, which is obviously GeSe 2 according to the diffraction pattern of GC 3 .…”
Section: Discussionsupporting
confidence: 68%
“…In previous a work, the controlled crystallization of 80GeSe 2 –20Ga 2 Se 3 has been successfully demonstrated 23,24 . These studies have shown two different regimes of crystallization at 380°C for different durations.…”
Section: Discussionmentioning
confidence: 90%
“…Even though several papers deal with thermodynamics to generate nanoparticles, the crystallization process still remains difficult to control and the reproducibility is a major concern. It is already known that a high content of CsCl could be dissolved in an antimony‐based glass, 5 resulting in the crystallization of submicron CsCl crystals that is rejected from the glassy matrix from an appropriate thermal treatment 6,7 . Glass–ceramics are usually obtained by a thermal treatment of bulk glass in a furnace at a predetermined temperature to allow nucleation and growth and during several hours.…”
Section: Introductionmentioning
confidence: 99%
“…The attempt to obtain chalcogenide glass–ceramics by crystallization treatment has been made since 1976 . Since then, the crystallization behavior of chalcogenide glasses have been investigated in some different systems such as GeS 2 –Ga 2 S 3 , GeSe 2 –Ga 2 Se 3 , GeSe 2 –Sb 2 Se 3 , and Ge–(Ga/Sb)–(Se/S)–MX (MX = alkali halide) . In these studies, chalcogenide glass–ceramics were obtained from base glasses using an appropriate heat treatment.…”
Section: Introductionmentioning
confidence: 99%